The The Influence of Entrepreneurial Self-Efficacy and Entrepreneurial Education on Entrepreneurial Persistence with Entrepreneurial Passion as an Intervening Variable : (Study on MSMEs in Samarinda City) - Syam, Syahrani; Fourqoniah, Finnah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study aims to determine whether there is an influence of entrepreneurial self-efficacy and entrepreneurial education on entrepreneurial persistence, with entrepreneurial passion as an intervening variable, among MSMEs in Samarinda City. The method used is a quantitative approach, with data collected through the distribution of questionnaires to 100 respondents. The sampling technique employed non-probability sampling using purposive sampling. The data obtained were analyzed using SmartPLS 3.0 through the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results of the study indicate that entrepreneurial self-efficacy and entrepreneurial passion have a positive and significant influence on entrepreneurial persistence. Similarly, there is a significant relationship between entrepreneurial self-efficacy and entrepreneurial passion, as well as the mediation of entrepreneurial passion in the relationship between entrepreneurial self-efficacy and entrepreneurial persistence. However, the results show no significant influence of entrepreneurial education on entrepreneurial passion, nor does entrepreneurial passion mediate the relationship between entrepreneurial education and entrepreneurial persistence. Entrepreneurial education has a negative and significant effect on entrepreneurial persistence. Therefore, entrepreneurs and the government need to promote more applied and sustainable education, self-confidence, and passion in supporting entrepreneurial persistence.